English language teaching in pesantren: challenges and strategies - Dhian Marita Sari (At Turots: Jurnal Pendidikan Islam, 2023)
English Language Teaching has spread to most institutions in Indonesia, including in Pesantren. This spread has resulted in certain challenges because English has been a compulsory subject for pesantren ‘s students. The present study investigated the teaching challenge and strategies to develop EFL Pesantren’s Students. In conducting the study, a literature review was conducted. Teaching English to pesantren students provides both challenges and strategies. Regarding the issue, this article identifies the challenges based on theories and research findings and then proposes several strategies for the difficulties which can be the references for pesantren institutions in English teaching and learning.